PP21 High Risk Class Medical Devices Evaluation In Germany: Another Arzneimittelmarkt-Neuordnungsgesetz? - Müller, Elvira; Oelze, Ilse-Barbara; Neeser, Kurt (International journal of technology assessment in health care, 2019)
Copyright © Cambridge University Press 20192019Cambridge University PressIntroductionIn 2011 the Arzneimittelmarkt-Neuordnungsgesetz (AMNOG) evaluation process for new drugs was implemented in Germany. Since then, the evidence requirements follow high standards and results impact reimbursement price negotiations. More recently, in 2016, a legal norm (§137h SGBV) to evaluate new treatment and diagnostic methods (MDs) of high risk classes by the Federal Joint Committee (G-BA) was introduced. The requirements, involved stakeholders, timing and results for both processes are outlined and compared.MethodsMethodological guidelines from G-BA and Institute for Quality and Efficiency in Health Care (IQWiG), consultations and evaluations for MDs according to §137h and for drugs according to AMNOG were reviewed and compared. Published assessment results were analyzed according the decision criteria and impact on price negotiations with Statutory Health Insurance.ResultsHospitals need to submit jointly with the manufacturer comparative evidence on clinical efficacy, safety and cost when applying for additional compensation (Neue Untersuchungs- und Behandlungsmethoden [NUB] application) for new high risk class MDs being subject to §137h. A fast track assessment by IQWiG/G-BA follows within four months resulting in benefit proven, potential benefit or no benefit compared to alternatives. The latter can lead to exclusion from reimbursement. Until now one MD was granted a benefit, two treatments were assigned a potential benefit and six MDs no benefit, while 55 percent of drugs evaluated under AMNOG were granted an additional benefit. Compared to drugs, the required evidence for MDs is similar. Whereas assessment time is shorter, manufacturers can seek advice from G-BA upfront for free and need to collaborate closely with hospitals.ConclusionsHalf of MDs examined did not qualify for an assessment under §137h. Unlike for drugs evaluated under AMNOG, the majority of new MDs failed to be granted potential benefit as a treatment alternative and might be excluded from reimbursement. Manufacturers are challenged to generate high quality, comparative evidence within their studies.